3D printed drug loaded nanomaterials for wound healing applications - Ashagrachew Tewabe Yayehrad; Ebrahim Abdella Siraj; Motlalepula Matsabisa; Gebremariam Birhanu (Regenerative Therapy, 2023)
Wounds are a stern healthcare concern in the growth of chronic disease conditions as they can increase healthcare costs and complicate internal and external health. Advancements in the current and newer management systems for wound healing should be in place to counter the health burden of wounds. Researchers discovered that two-dimensional (2D) media lacks appropriate real-life detection of cellular matter as these have highly complicated and diverse structures, compositions, and interactions. Hence, innovation towards three-dimensional (3D) media is called to conquer the high-level assessment and characterization in vivo using new technologies. The application of modern wound dressings prepared from a degenerated natural tissue, biodegradable biopolymer, synthetic polymer, or a composite of these materials in wound healing is currently an area of innovation in tissue regeneration medicine. Moreover, the integration of 3D printing and nanomaterial science is a promising approach with the potential for individualized, flexible, and precise technology for wound care approaches. This review encompasses the outcomes of various investigations on recent advances in 3D-printed drug-loaded natural, synthetic, and composite nanomaterials for wound healing. The challenges associated with their fabrication, clinical application progress, and future perspectives are also addressed.